Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres